Autophagy differentially controls plant basal immunity to biotrophic and necrotrophic pathogens. - Lenz, H; Haller, E; Melzer, E; Kober, K; Wurster, K; Stahl, M; Bassham, D; Vierstra, R; Parker, J; Bautor, J; Molina, A; Escudero, V; et al. (2011)
In plants, autophagy has been assigned 'pro-death' and 'pro-survival' roles in controlling programmed cell death associated with microbial effector-triggered immunity. The role of autophagy in basal immunity to virulent pathogens has not been addressed systematically, however. Using several autophagy-deficient (atg) genotypes, we determined the function of autophagy in basal plant immunity. Arabidopsis mutants lacking ATG5, ATG10 and ATG18a develop spreading necrosis upon infection with the necrotrophic fungal pathogen, Alternaria brassicicola, which is accompanied by the production of reactive oxygen intermediates and by enhanced hyphal growth. Likewise, treatment with the fungal toxin fumonisin B1 causes spreading lesion formation in atg mutant genotypes. We suggest that autophagy constitutes a 'pro-survival' mechanism that controls the containment of host tissue-destructive microbial infections. In contrast, atg plants do not show spreading necrosis, but exhibit marked resistance against the virulent biotrophic phytopathogen, Pseudomonas syringae pv. tomato. Inducible defenses associated with basal plant immunity, such as callose production or mitogen-activated protein kinase activation, were unaltered in atg genotypes. However, phytohormone analysis revealed that salicylic acid (SA) levels in non-infected and bacteria-infected atg plants were slightly higher than those in Col-0 plants, and were accompanied by elevated SA-dependent gene expression and camalexin production. This suggests that previously undetected moderate infection-induced rises in SA result in measurably enhanced bacterial resistance, and that autophagy negatively controls SA-dependent defenses and basal immunity to bacterial infection. We infer that the way in which autophagy contributes to plant immunity to different pathogens is mechanistically diverse, and thus resembles the complex role of this process in animal innate immunity.